Analysis of the Influence of Customer Reviews and Customer Trust on Customer Loyalty through Customer Satisfaction as an Intervening Variable - Fitriani, Lili; Rois, Tatang; Seliana, Sela (International Journal Administration, Business & Organization, 2024)
The aim of this study is to analyze influence between customer reviews and customer trust on customer loyalty with customer satisfaction as an intervening variable. This study used descriptive and quantitative methods. Sampling was determined using a non-probability sampling technique with size of sample is 130 respondents who are Shopee users in Ciayumajakuning. Data collection by questionnaires to conducted through the distribution sample, and measurements used an interval scale. Data analysis was performed using path analysis. The research results indicate that customer reviews has a negative and insignificant impact on customer satisfaction. Customer trust has a positive and significant impact on customer satisfaction. Customer reviews have a positive and significant impact on customer loyalty. Customer trust has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant impact on customer loyalty. Customer satisfaction can not mediate the correlation between customer reviews and customer loyalty. Customer satisfaction mediating correlation in the middle of customer trust and customer loyalty. The implication companies should focus directly on managing customer reviews and experiences to effectively influence loyalty without relying on satisfaction as an intermediary. On the other hand, to enhance overall loyalty, building strong trust is crucial, as trust can increase customer satisfaction, which in turn strengthens loyalty based on that trust.